2011
DOI: 10.1007/s13199-011-0107-5
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungal phylogeny-related interactions with a non-host

Abstract: Arbuscular mycorrhizal fungi (AMF) form symbiotic relationships with most vascular plants including some gymnosperm species. Although species in the gymnosperm family Pinaceae normally develop ectomycorrhizal associations, AMF hyphae and vesicles, typical of members of the Suborder Glomineae, have been reported in the roots of some Pinaceae species. However, it is not known whether AMF belonging to various species and suborders are able to colonize roots of Pinaceae species and to what extent this influences t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
1
9
3
Order By: Relevance
“…Large number of small vacuoles were observed as a response to the heavy colonization by G. mosseae ( Figure 1B), these vacuoles act as a viable propagules and storage structures (Plenchette and Strullu, 2003). The current results are closed to that reported by Wagg et al (2011) who found that Glomus intraradices produced large numbers of vesicles in pine (Pinus aphremphous) forest tree.…”
Section: Discussioncontrasting
confidence: 53%
“…Large number of small vacuoles were observed as a response to the heavy colonization by G. mosseae ( Figure 1B), these vacuoles act as a viable propagules and storage structures (Plenchette and Strullu, 2003). The current results are closed to that reported by Wagg et al (2011) who found that Glomus intraradices produced large numbers of vesicles in pine (Pinus aphremphous) forest tree.…”
Section: Discussioncontrasting
confidence: 53%
“…However, greenhouse studies have shown that ectomycorrhizal plants can outcompete arbuscular mycorrhizal plants for a single resource pool (Pederson, Sylvia, & Shilling, ), and evidence from monodominant tropical forests suggests that ectomycorrhizal fungi may cause local competitive exclusion of arbuscular mycorrhizal plants (Corrales, Mangan, Turner, & Dalling, ; McGuire, ). Wagg, Antunes, and Peterson () showed that the presence of AM fungi may suppress growth of ectomycorrhizal plants. Thus, it is generally uncertain how contrasting mycorrhizal associations will influence plant–plant competition.…”
Section: Introductionmentioning
confidence: 99%
“…There are reports of AMF colonization in gymnosperms. Several authors [7, 11–15] have reported the presence of AMF hyphae and vesicles in the roots of Pseudotsuga menziesii, Tsuga, Abies and P. muricata . These reports indicate that although ectomycorrhizal symbioses are predominant in the structure and function of gymnosperm roots, AMF are present in the roots of these trees as well.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are some reports of colonization by AMF in Pinaceae [7, 8, 9]. For example, the presence of AMF vesicles in the roots of Pseudotsuga menziesii has been reported [15]. Additionally, several authors have reported AMF vesicles and hyphae in the roots of five other species of Pinaceae in the genera Tsuga [11, 12, 13], Pinus [14, 7, 15] and Abies [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation